Teşbih ve Tecsim Karşısında Bir Hadisçi; Celaluddin Es-Suyuti - Çakin, Kamil (Dinî araştırmalar, 2001)
Al-Suyuti was a famous hadith scholar who lived between (849- 911 h). He had composed a lot of written works in differen tfields of the hadith. One of his works is "Ta'vil al-Ahadith al-Muhime li al-Tashbih" which was assigned to God's attributes. In his work, al-Suyuti investigated some hadiths which expresses God himself as a personality has some organs (teşbih = anthropomorphism) and as a material being (tecsim = materialization). And he interpreted these hadiths. In spite of the predecessors in hadith being far from interpreting these hadiths, he prefered commentaring them in rational method. In this work, it has been studied the commentator character of al-Suyuti and his methods in that commentary